The global canopy : a good practice guide. - McLaughlin, Patricia; Mills, Anthony; Davis, Peter; Saha, Swapan; Poronnik, Philip; Hadgraft, Roger; Bedford, Anthony; Hinton, Tina; Baglin, James; Chester, Andrea; Lawson, Justine (Australia. Dept of Education and Training, 2016)
This document is a guide for university educators of undergraduate domestic and international students. It embodies the objectives of the Global Canopy Project - to create awareness and provide case studies examples of global mobility activities across a range of disciplines and university contexts. The range of case studies presented here is diverse in student cohort, environment, discipline and university context. This diversity is deliberate and the authors hope will allow the widest possible range of academics to engage with and emulate some of the ideas and practices presented in their own institutions. The case studies details approaches within disciplines to focus domestic students on themes of global mobility and to utilise the experiences of international students within these disciplines to work with domestic students in learning activities focused upon this mobility. [Preface, ed]